2015
DOI: 10.1016/j.dib.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Data in support of comparative physiology and proteomic analysis of two wheat genotypes contrasting in drought tolerance

Abstract: Here, we present the data from a comparative physiology and proteomics approach used to analyze the response of two wheat genotypes (SERI M 82 (SE) and SW89.5193/kAu2 (SW)) with contrasting responses to drought stress. Proteomic analysis resulted in identification of 49 unique proteins with significant change in abundance (2-fold) under water shortage in roots and leaves. Gene ontology analysis of drought-responsive proteins (DRPs) suggested an induction of proteins related to cell wall biogenesis, ATP synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…In this study, the abundance of GST (spot 19, 20 and 32) ( Table 2 and Fig. 4) was the highest when NH4 + was the sole nitrogen source in solution, implying that GST may play a key role in the resistance to NH4 + toxicity, as previously reported for plants under drought stress (Faghani et al, 2015), salinity stress (Wei et al, 2010), cold stress (Badowiec and Weidner, 2014) or pathogen attack (Han et al, 2016). This suggests that GST is widely involved in plant responses to biotic and abiotic stresses.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, the abundance of GST (spot 19, 20 and 32) ( Table 2 and Fig. 4) was the highest when NH4 + was the sole nitrogen source in solution, implying that GST may play a key role in the resistance to NH4 + toxicity, as previously reported for plants under drought stress (Faghani et al, 2015), salinity stress (Wei et al, 2010), cold stress (Badowiec and Weidner, 2014) or pathogen attack (Han et al, 2016). This suggests that GST is widely involved in plant responses to biotic and abiotic stresses.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, two Arabidopsis GLPs (AT4G14630; GLP9 and AT3G62020; GLP10) showed stronger binding with the methylated calmodulin (CaM) compared to the unmethylated CaM in presence of calcium indicating the probable involvement of GLPs in root development (Banerjee et al 2013). Differential accumulation of three germin-like proteins (Q9SM34, C3UZE6, and Q9SM34) was reported during drought stress among the sensitive and tolerant wheat roots using nano LC-ESI-MS/MS analysis (Faghani et al 2015). Among those three proteins, Q9SM34 showed top hit entry from the list of the identified protein in the corresponding spot.…”
Section: Expression and Biological Functions Of Glps In Root Tissuesmentioning
confidence: 96%
“…Recently many reports on changes in plant proteome under abiotic stress in large number of plant species have been published. Successful proteomics study for drought stress were reported in wheat [15]; Brassica napus [16]; maize [17]; barley [18] and wild watermelon [19]. Under drought stress plants expresses different proteins, not specifically related to drought, other than induced due to the damages of cell.…”
Section: Introductionmentioning
confidence: 99%